2015
DOI: 10.1111/ped.12500
|View full text |Cite
|
Sign up to set email alerts
|

Transient abnormal myelopoiesis in non‐Down syndrome neonate

Abstract: We encountered a case of neonatal acute megakaryoblastic leukemia not associated with Down syndrome (DS). Molecular cytogenetic analysis of leukemic blast cells indicated that increased blast cell status was caused by transient abnormal myelopoiesis with trisomy 21 and GATA1 mutation. Based on these molecular cytogenetic data, intensive chemotherapy was avoided, and the patient was successfully cured with low-dose cytarabine. Morphologically, leukemic blast cells of acute megakaryoblastic leukemia in a non-DS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…performed a literature review of 14 patients with TAM that was not associated with DS and reported that GATA1 mutations were analyzed in only eight patients, all of whom had GATA1 mutations as well as trisomy 21 in leukemic blasts, indicating that the biology of TAM without constitutional trisomy 21 was similar to that of TAM with constitutional trisomy 21/DS . After the report of Rozen et al., there have also been several case reports of TAM without constitutional trisomy 21 but harboring both trisomy 21 and GATA1 mutations in leukemic blasts . Here, we present the cytogenetic findings and GATA1 mutation status of a series of 17 patients with TAM and nonconstitutional trisomy 21 who had been tested for GATA1 mutations at a single institute.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…performed a literature review of 14 patients with TAM that was not associated with DS and reported that GATA1 mutations were analyzed in only eight patients, all of whom had GATA1 mutations as well as trisomy 21 in leukemic blasts, indicating that the biology of TAM without constitutional trisomy 21 was similar to that of TAM with constitutional trisomy 21/DS . After the report of Rozen et al., there have also been several case reports of TAM without constitutional trisomy 21 but harboring both trisomy 21 and GATA1 mutations in leukemic blasts . Here, we present the cytogenetic findings and GATA1 mutation status of a series of 17 patients with TAM and nonconstitutional trisomy 21 who had been tested for GATA1 mutations at a single institute.…”
Section: Discussionmentioning
confidence: 83%
“…19 After the report of Rozen et al, there have also been several case reports of TAM without constitutional trisomy 21 but harboring both trisomy 21 and GATA1 mutations in leukemic blasts. [21][22][23][24] Here, we present the cytogenetic findings and GATA1 mutation status of a series of 17 patients with TAM and nonconstitutional trisomy 21 who had been tested for GATA1 mutations at a single institute. All 17 patients harbored both trisomy 21 and GATA1 mutations in leukemic blasts, clearly showing that the molecular pathogenesis is common between TAM with and without constitutional trisomy 21.…”
Section: Discussionmentioning
confidence: 99%
“…In the event that a newborn with a normal karyotype and trisomy 21 only in blasts presents symptoms typical of congenital leukemia, the best approach is to ‘wait and see’ and to perform GATA1 gene sequencing as soon as possible. If the patient's condition deteriorates, it may be advisable to commence low-dose chemotherapy (17). The presence of a GATA1 mutation can confirm a diagnosis of TAM and therefore determine the non-therapeutic approach.…”
Section: Discussionmentioning
confidence: 99%